2016
DOI: 10.3892/mmr.2016.5325
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in Neuregulin-1 signaling in major brain regions in a lipopolysaccharide-induced neuroinflammation mouse model

Abstract: Neuregulin 1 (Nrg1) is involved in multiple biological processes in the nervous system. The present study investigated changes in Nrg1 signaling in the major brain regions of mice subjected to lipopolysaccharide (LPS)-induced neuroinflammation. At 24 h post-intraperitoneal injection of LPS, mouse brain tissues, including tissues from the cortex, striatum, hippocampus and hypothalamus, were collected. Reverse transcription-polymerase chain reaction was used to determine the expression of Nrg1 and its receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Previous studies have shown that LPS can significantly increase phosphorylation levels of ERK in the hippocampus of mice [41,42]. At the same time, one study demonstrated that LPS did not affect ERK phosphorylation in the hippocampus of mice [43]. In our study, we observed that LPS did not affect the phosphorylation of ERK in the hippocampus.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have shown that LPS can significantly increase phosphorylation levels of ERK in the hippocampus of mice [41,42]. At the same time, one study demonstrated that LPS did not affect ERK phosphorylation in the hippocampus of mice [43]. In our study, we observed that LPS did not affect the phosphorylation of ERK in the hippocampus.…”
Section: Discussionsupporting
confidence: 58%
“…Neuregulin 1 is a key regulator of Schwann cell migration, proliferation, and survival (Heermann & Schwab, ). Recently, systemic TLR4 activation was shown to alter neuregulin 1 expression in the brain (Yang et al, ), thus it is possible that TLR4 activation in the CNS can influence Schwann cell recruitment via neuregulin signaling. Our recent data implicate TLR4 signaling in regulating growth factor and cytokine expression in the damaged spinal cord (Church et al, ), therefore it is likely that E6020 treatment altered the inflammatory environment after lysolecithin demyelination to favor Schwann cell recruitment and survival.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated different changes on Akt1 signaling in major mouse brain regions in response to LPS. The Akt1 level was significantly increased in the striatum, no changes in the cortex and hypothalamus, and an increase in hippocampus although no significant difference was found compared with the control mice [39]. Since most of cerebral I/R animal model studies were performed in the brain tissue, especially in the hippocampus, further studies looking at the level of Akt in blood are needed.…”
Section: Discussionmentioning
confidence: 99%